2015
DOI: 10.3892/mmr.2015.4188
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microRNA-155 relieves sepsis-induced liver injury through inactivating the JAK/STAT pathway

Abstract: The present study aimed to investigate whether the microRNA (miR)‑155 inhibitor has an anti‑inflammatory effect on sepsis‑associated liver injury and whether this effect is associated with the activity of the janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway. BALB/c mice were randomly divided into three groups (n=40 per group): Control, lipopolysaccharide (LPS) and miR‑155 inhibitor plus LPS groups. Liver injury was induced by injection of LPS (20 mg kg‑1). In the inhibitor plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…The Jak-STAT signaling pathway, T cell receptor signaling pathway, and natural killer cell-mediated pathway appeared in the downregulated gene set. The potential impact of these pathways in sepsis has already been stated in published studies [22][23][24][25][26]. The results showed that genes participating in immune and inflammatory responses have mixed differential expression patterns of both up-and downregulation.…”
Section: Discussionmentioning
confidence: 56%
“…The Jak-STAT signaling pathway, T cell receptor signaling pathway, and natural killer cell-mediated pathway appeared in the downregulated gene set. The potential impact of these pathways in sepsis has already been stated in published studies [22][23][24][25][26]. The results showed that genes participating in immune and inflammatory responses have mixed differential expression patterns of both up-and downregulation.…”
Section: Discussionmentioning
confidence: 56%
“…It should be noted that inhibition of miR-155 improves outcomes in experimental peritonitis [ 38 , 39 ]. miRNAs have not yet been successfully used directly as a therapeutic modality in humans; however, some miRNAs are under investigation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that miR-155-mediated suppression of SOCS1 has biological significance in infection and autoimmunity [60]. This interaction has for example been implicated in the reduction in LPS-induced liver injury and reduced TNFα production observed with a miR-155 inhibitor in a mouse model [61]. In other contexts, however, the effect of miR-155 on SOCS1 may in fact be protective.…”
Section: Discussionmentioning
confidence: 99%